DESIGN OF ULTRA WIDEBAND FILTER - MOHAMAD YUSOFF, MOHD NOORAMIN (Universiti Teknologi PETRONAS, 2011)
Ultrawideband (UWB) filter is one type of filter that has been developed since several years ago. The frequency band released by Communications Commission (FCC) of the United States in 2002 for UWB commercial communication is 3.1-10.6 GHz. Having wide bandwidth frequency of 7.5 GHz, it provides several advantages like capability to support a high transmission data rate up to 500 Mb/s. Several teclrniques have been discovered during past years to develop this system. However, the problem that we face today there is no analytical model has been developed so far. Therefore, my project is aiming to develop analytical model for Ultra Wideband filter that come out with MMR. To achieve this objective, I am using even and odd mode analysis. This even and odd mode analysis is realized based on symmetrical network circuit of microstrip, which in this case we use multi-mode resonator (MMR). The purpose of doing even and odd mode analysis is to find the Yeven and Yodd, hence the equations of scattering parameter S12 and Su can be determined later on. After done mathematical analysis, the ideal plots of S-Pararneter for UWB are simulated in both ADS and Matlab. The simulations in both ADS and Matlab will be compared to prove the mathematical analysis. If same result produced, means that the mathematical analysis done is valid and the design of microstrip is continued in A WR or ADS for fabrication purpose. Otherwise, the results then will be analyzed and further investigated